2022
DOI: 10.1002/app.52862
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hydroxyapatite filler on biodegradable poly(sorbitol sebacate malate) composites

Abstract: Biodegradable poly(sorbitol sebacate malate)/hydroxyapatite (PSSM/HA) composites were successfully synthesized through one step catalyst‐free polycondensation of sorbitol, sebacic acid, malic acid, and HA powder as filler for the composites. The addition of HA improved the tensile modulus and strength of the materials compared with pure PSSM. The elongation at break of the composites was slightly reduced with increasing HA content. The PSSM and HA showed good compatibility, which was evidenced by good distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Sorbitol-based polyesters have garnered considerable attention in recent years due to their versatile properties, renewability, and potential applications in various industries. 103 Sorbitol is a natural hexitol found in fruits. Its unique properties, such as being tooth-friendly and hygroscopic, make it a valuable component in food, pharmaceutical, and cosmetic products.…”
Section: Bio-polyesters Based On Polyolsmentioning
confidence: 99%
“…Sorbitol-based polyesters have garnered considerable attention in recent years due to their versatile properties, renewability, and potential applications in various industries. 103 Sorbitol is a natural hexitol found in fruits. Its unique properties, such as being tooth-friendly and hygroscopic, make it a valuable component in food, pharmaceutical, and cosmetic products.…”
Section: Bio-polyesters Based On Polyolsmentioning
confidence: 99%
“…25,26 Moreover, it has been observed that this particular family of bioelastomers can be combined with minerals, vitamins, and drugs to create suitable composites for drug delivery and tissue engineering applications. 24,[27][28][29][30] Through the blending of poly (glycerol sebacate) with polycaprolactone, it has been demonstrated that it is possible to maintain biocompatibility at a level comparable to pure poly (glycerol sebacate) while also achieving a wide range of mechanical properties. 31 Piatek-Hnat et al studied the effects of radiation modification of sugar alcohol-based bioelastomers and reported that these polymers are well-suited for radiation modification.…”
Section: Introductionmentioning
confidence: 99%